Comparative analysis of maternal and neonatal outcomes between elective and emergency caesarean section at a single tertiary hospital: a retrospective COHORT study - Riyami, Nihal M. Al; Shereiqi , Shurooq S. Al; Pillai , Silja A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Caesarean section rates have been increasing worldwide despite it’s known complications. The aim of this study was to determine maternal and neonatal complications related to caesarean section at Sultan Qaboos University Hospital (SQUH) and to compare the outcomes between emergency and elective caesarean sections. Methods: This retrospective cohort study was conducted in the department of obstetrics and gynecology at SQUH from 1st January 2016 to 31st December 2016. This comparative study involved 300 women who underwent caesarean section, 150 in elective caesarean section group and 150 in emergency caesarean section group. Results: The mean maternal age was 29.66 (±4.96) and 33.22 (±4.63) years in the elective and emergency caesarean section groups respectively (p=001). The main risk factor for both the groups was maternal diabetes and the most common indication was previous caesarean section. Hypotension related anesthetic complication was noted more in elective caesarean section (15.3%) than in emergency caesarean section group (4.0%) with p value=0.002. Post-partum fever was seen in 12.0% of women in emergency group as compared to 4% in elective group (p=0.019). Anemia was observed in 79.2% and 65.3% in emergency and elective groups respectively (p=0.011). Respiratory distress syndrome and transient tachypnea of the newborn were the main neonatal complications in both groups. Conclusions: There was no significant difference between emergency and elective caesarean section related maternal and neonatal complications except for transient intraoperative hypotension, maternal postoperative febrile morbidity and anemia. Future prospective studies including larger sample size and multiple centers is recommended.